Management of Hypothyroidism through Yoga Intervention: A Study of Yogic Approaches - Rani, Pooja; Singh, Sandeep (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Hypothyroidism is one of the most common health problems that are caused by the dysfunction of the thyroid gland. It is considered to be a widespread health problem in India and around the world and is more common among women. The aggregate prevalence of hypothyroidism in India is 10%, with a prevalence of 15.8% among women. In modern medicine, the synthetic thyroid hormone levothyroxine is used on a regular basis to treat hypothyroidism (Levothroid, Synthroid, and others). A patient may become permanently dependent on these medications. Aim: Yoga-based practises have been demonstrated to help manage hypothyroid symptoms. There is limited research on the impact of yoga on thyroid diseases, despite the fact that it has been proposed that yoga may help to rejuvenate thyroid function. Materials and methods: In this review, we looked at the basic principles of the Pancha Kosha (five sheaths of human existence) concepts from the Indian scripture Taittiriya Upanishad, as well as the pathophysiology of a disease from the Yoga approach, Yoga Vasishta’s Adhi (mind-originated) and Vyadhi (ailment/disease) concepts. Result: Based on these perspectives and previous research, we offer an effective yogic management for hypothyroidism to improve the quality of life of a hypothyroid patient.